Electronic trade and prospects for its development in the world economy - V. K. Shaidullina (Вестник университета)
The wide distribution of information and communication technologies has led to the development of e-commerce. In the B2B segment, the use of electronic sales methods has until recently been more common due to legal requirements, that restrict cash payments. Existing informational, technological and technical capabilities make it possible to expand electronic forms of trade to almost all segments of market relations. The retrospective and growth prospects of e-commerce in the global economy has been considered in the article. Through use of statistical and forecast data, the main players of the e-commerce market in the country as of the current moment and in the near future perspective have been identified. The key factors of the avalanche-like growth of online commerce in the modern world economy have been considered.